USE OF SECONDARY ENERGY RESOURCES - Fozilova Mohira Soyibjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Secondary energy resources are derived from the conversion or transformation of primary energy sources into more accessible and usable forms. These include electricity, hydrogen, refined fuels, biogas, and district heating or cooling systems, among others. Secondary energy plays a crucial role in modern energy systems by providing flexibility, efficiency, and convenience across various sectors, including transportation, heating, electricity generation, and industrial applications. The conversion processes for these resources—such as burning fossil fuels, nuclear fission, and renewable energy technologies—help optimize energy use and storage. While secondary energy resources offer numerous benefits, including enhanced energy storage capabilities and cleaner alternatives to traditional fuels, they also pose challenges related to environmental impact, infrastructure costs, and energy losses during conversion. This article explores the types, conversion processes, applications, and associated challenges of secondary energy resources, highlighting their importance in achieving a more sustainable energy future.